Exercise in the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) era: A Question and answer session with the experts endorsed by the section of Sports Cardiology & Exercise of the European Association of Preventive Cardiology (EAPC) - Bhatia, R. T.; Marwaha, S.; Malhotra, A.; Iqbal, Z.; Hughes, C.; Börjesson, M.; Niebauer, J.; Pelliccia, A.; Schmied, C.; Serratosa, L.; Papadakis, M.; Sharma, S. (European Journal of Preventive Cardiology, 2020)
Regular exercise has multiple benefits for physical and mental health, including the body`s ability to combat infections. The current COVID-19 pandemic and the social distancing measures employed to curtail the impact of the infection are likely to reduce the amount of usual physical activity being performed by most individuals, including habitual exercisers. The uncertainties relating to the impact of the SARS-CoV-2 virus on the heart may cause increased anxiety, particularly in athletes who need to sustain a vigorous exercise regime in order to maintain their skills and fitness in preparation for return to competition after a short re-training period. The aim of this document is to provide practical answers to pertinent questions being posed by the sporting community, in an attempt to offer reassurance, promote safe participation in exercise during as well as after the COVID-19 pandemic and provide a framework of management for physicians caring for athletes.